Comportamiento agronomico del cultivo de cebolla de rama (Allium fistulosum l), con diferentes abonos orgánicos, en el colegio Pueblo Nuevo El Empalme, año 2014 - Pio Macay, Luis Alberto (2015)
This research was conducted at school Pueblo Nuevo. Guayas parish 10 miles of Canton right margin Empalme, Guayas Province. Its geographical location is 1 59`25 "south latitude, 79th 34`25" west longitude at an altitude of 85msnm. The investigation lasted 240 days. Variables valued at 60, 90, 120 and 180 days after sowing were leaf length and number of leaves, which were performed at the end of the culture harvest are: stem diameter, stem length, number of tillers, plant height, weight of 12 branches (g) and yield in kg / plot at harvest. Design of randomized complete block (RCBD) with seven treatments and four replications. To determine the statistical difference test Tukey multiple range up to 95% was used. Of the evaluated variables had better performance, treatment with the dosage of 5kg / m² with manure vermicompost. The number of tillers was higher with the application of vermicompost with a dosage of 5 kg / m², a total of 15.35 tiller per plant. Increased production was obtained with the application of vermicompost 5kg / m² 3.38Kg / m